Arkeologi Komunitas: Daya Dukung Pengembangan Pengetahuan Arkeologi melalui Media Digital - Saswal Ukba; M. Sabri; Nurul Afni Sya’adah; Cahayatunnisa; Argi Arafat; Irsyad Leihitu; Muhammad Satok Yusuf (AMERTA, 2026)
Abstract. Community Archaeology: Supporting the Development of Archaeological Knowledge through Digital Media. The growing presence of community archaeology today further strengthens the position of archaeological scholarship as a field that is increasingly accessible to the public. The role of community archaeology serves as an alternative mechanism for connecting cultural heritage values in ways that are easily understood and beneficial in supporting archaeological work. This condition is reinforced by advancements in information technology, which can be accessed widely through social media. Accordingly, this study employs digital social media data specifically instagram and facebook as primary data, along with a literature review that gathers relevant sources concerning the position of community archaeology as secondary data. The data analysis conducted is descriptive in nature. The aim of this research is to identify the significance and role of community archaeology in the development of archaeological science. The findings indicate that community archaeology plays an essential role in bridging archaeological knowledge so that it becomes more comprehensible to the wider public through digital information technology and social media. In addition, community archaeology can also contribute to strengthening human resource capacity and knowledge through publicly formed communities. Keywords: Community archaeology, Social media, Archaeological work, Supportive capacity   Abstrak. Kehadiran arkeologi komunitas dewasa ini semakin menguatkan kedudukan pengembangan ilmu arkeologi untuk mudah diakses oleh publik. Peran arkeologi komunitas dapat menjadi salah satu alternatif untuk menghubungkan nilai-nilai warisan budaya untuk mudah dipahami dan dipetik manfaatnya dalam mendukung kerja-kerja arkeologi. Kondisi ini didukung dengan kemajuan teknologi informasi yang dapat diakses oleh siapa saja lewat media sosial. Untuk itu, penelitian ini menggunakan data digital media sosial berupa instagram dan facebook sebagai data primer dan studi kepustakaan dengan mengumpulkan sumber kajian yang relevan dengan kedudukan arkeologi komunitas sebagai data sekunder nya. Adapun analisis data yang digunakan yaitu bersifat deskriptif. Penelitian ini bertujuan untuk mengetahui kepentingan dan peran arkeologi komunitas dalam pengembangan ilmu arkeologi. Berdasarkan hasil penelitian dapat diketahui bahwa arkeologi komunitas memiliki peran penting untuk menghubungkan pengetahuan arkeologi untuk mudah dipahami oleh masyarakat umum melalui teknologi informasi digital media sosial. Selain itu, arkeologi komunitas dapat berperan pula pada sektor peningkatan kemampuan dan pengetahuan sumber daya manusia melalui komunitas yang di bentuk oleh publik. Kata kunci: Arkeologi komunitas, Media sosial, Kerja arkeologi, Daya dukung